An Exploratory Study of the Protected Area Management Policies in Odisha - Mishra, Brajaraja (Indian Forester, 2013)
This study focuses on the response of the Government of Odisha in particular and the Government of India in general in the context of the recent global paradigm shift with respect to the protected area management policies. An account of the welfare loss due to the implementation of the various conservation acts as against the potential benefits of the implementation of the Eco-Development Project and the Forest Rights Act, 2006, shows that the paradigm shift has significantly improved social welfare and that more concerted efforts are needed for their better implementation. The study also emphasizes the significance of value judgment principles that need to be adopted by the stakeholders on the basis of ethics and justice in terms of creating a better scope for achieving sustainable development.